1981
DOI: 10.1016/s0006-3495(81)84867-9
|View full text |Cite
|
Sign up to set email alerts
|

Transport across homoporous and heteroporous membranes in nonideal, nondilute solutions. II. Inequality of phenomenological and tracer solute permeabilities

Abstract: The phenomenological solute permeability (omega p) of a membrane measures the flux of solute across it when the concentrations of the solutions on the two sides of the membrane differ. The relationship between omega p and the the conventionally measured tracer permeability (omega T) is examined for homoporous and heteroporous (parallel path) membranes in nonideal, nondilute solutions and in the presence of boundary layers. In general, omega p and omega T are not equal; therefore, predictions of transmembrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In general, one expects intermediate behavior, such that 0 < σ oh < 1. Values of σ oh for various solutes have been measured for cell membranes [4,5], capillary walls [6,7], and synthetic membranes [8][9][10], to cite a few examples. From a thermodynamic viewpoint, osmosis is due to an imbalance in the chemical potential of the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…In general, one expects intermediate behavior, such that 0 < σ oh < 1. Values of σ oh for various solutes have been measured for cell membranes [4,5], capillary walls [6,7], and synthetic membranes [8][9][10], to cite a few examples. From a thermodynamic viewpoint, osmosis is due to an imbalance in the chemical potential of the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of osmotic pressure differences, pressure creates a steady state flow for which the equations f Measurements of crs and erf in a heteroporous membrane have been made by Friedman & Meyer (1981), who studied the concentration dependence of the coefficients and concluded that <rs and (Tf converge in dilute solution. However, extrapolation of their data to low concentration does not really show unequivocal convergence, especially in the light of the above discussion that owing to the porosity distribution ers and <rf can be roughly equal in heteroporous polymer membranes without there being any underlying Onsager symmetry.…”
Section: Appe N D Ix a D Erivatio N Of Crs In Frictional Theorymentioning
confidence: 99%
“…To describe transport phenomena in biological and technical systems, models developed in the framework of nonequilibrium thermodynamics [8][9][10][11][12], diffusion models [13,14], and friction [15][16][17]; models developed in the framework of statistical physics [18][19][20]; and models developed as part of the network thermodynamics [21][22][23][24][25][26] are used. In order to characterize the relationship between generalized streams of liquid and solutes and their generalized driving forces, which are derived from the electrochemical and/or chemical affinity gradient, the thermodynamics of Onsager are used [9,11,27,28].…”
Section: Introductionmentioning
confidence: 99%